When eaudiobook The scientific secrets of perfect timing. - Pink, Daniel H. (Penguin Audio, 2018)
The instant New York Times Bestseller #1 Wall Street Journal Business Bestseller Instant Washington Post Bestseller "Brims with a surprising amount of insight and practical advice." — The Wall Street Journal Daniel H. Pink, the #1 bestselling author of Drive and To Sell Is Human , unlocks the scientific secrets to good timing to help you flourish at work, at school, and at home.  Everyone knows that timing is everything. But we don't know much about timing itself. Our lives are a never-ending stream of "when" decisions: when to start a business, schedule a class, get serious about a person. Yet we make those decisions based on intuition and guesswork. Timing, it's often assumed, is an art. In W hen: The Scientific Secrets of Perfect Timing , Pink shows that timing is really a science. Drawing on a rich trove of research from psychology, biology, and economics, Pink reveals how best to live, work, and succeed. How can we use the hidden patterns of the day to build the ideal schedule? Why do certain breaks dramatically improve student test scores? How can we turn a stumbling beginning into a fresh start? Why should we avoid going to the hospital in the afternoon? Why is singing in time with other people as good for you as exercise? And what is the ideal time to quit a job, switch careers, or get married? In When , Pink distills cutting-edge research and data on timing and synthesizes them into a fascinating, readable narrative packed with irresistible stories and practical takeaways that give readers compelling insights into how we can live richer, more engaged lives.